Cardiac autonomic profile in cervical spinal cord injury subjects practitioners of the physical exercise - Edgar William Martins; Roberto Magalhães; Moacir Marocolo; Alex Souto Maior (Universidade Estadual de Maringá, 2018)
The aim was investigate the time-course of cardiac autonomic response in men with incomplete cervical spinal cord injury (SCI) practitioners or not of physical exercise. Twenty men were separated into three groups: control group without SCI (CON; 28.3 ± 4.5 yrs; 178.4 ± 6.5 cm; 82.1 ± 6.8 kg; n=8), regularly engaged in strength training and low aerobic training; exercise group with cervical SCI (EG, 32.3 ± 4.5 yrs, 175.1 ± 5.3 cm, 73.6 ± 9.6 Kg; n=8) that practiced wheelchair rugby and sedentary group with cervical SCI (SG, 30.8 ± 5.3 yrs, 173.4 ± 10.1 cm, 69.7 ± 7.1 Kg; n=4) who did not practice physical exercise. Heart rate variability variables were calculated from ECG, in rest. CON showed high values compared to EG and SG of: standard deviation of R-R intervals (SDNN), proportion of adjacent R-R intervals differing by more than 50 ms, number of interval differences of successive NN intervals greater than 50 ms, root mean square of successive differences and the high-frequency spectral power. SDNN was significantly lower in EG compared to CON. changes in cardiac autonomic function could be noted in subjects with cervical SCI regularly engaged in an exercise program.